Magnetostratigraphy of the Makran Margin Sediments - Tabrez, A. R. (Journal of Himalayan Earth Sciences, 1997)
Five piston cores were recovered from IV-S slope transect across the Makran Continental Margin during the joint research programme between Pakistan and The Netherlands in 1992. These cores are from upper slope region (Water Depth 1325 m; 5.5 m length). Three are from mid-slope basins (Water Depth 1768 to 2482 m; 5.5 to 14 m length) and two from abyssal plain (Water Depth 3274 m; 10.5 m length). Oxygen Isotope stratigraphy and magnetostratigraphy studies of the two cores (MKM - 469from mid-slope and MKM-472 from abyssal plain) reveal the climatic change leading to more dominant monsoonal condition in the early Holocene and hence an increased supply of terrigenous material including magnetic grains. Observed short duration palaeomagnetic excursions (6000-8000 yrs B. P and 26000 yrs B.P) noted in both cores reflect true geomagnetic field behaviour on the Makran Margin.